Factors Affecting Consumers’ Impulse Buying Behavior in Thai Nguyen City, Vietnam - Ma Toan Thang (Randwick International of Social Science Journal, 2024)
The study uses primary data collected from a structured survey of 300 customers at supermarkets and shopping malls in Thai Nguyen city, Vietnam. Using the exploratory factor analysis and a multiple regression model, the study analyzed factors affecting consumers' impulse buying behavior. Results show that five main factors having significantly positive impacts on impulse buying behavior of customers in Thai Nguyen city include availability of time and money, music and promotions, shopping enjoyment tendency, in-store factors, and surroundings. However, the findings on impulse buying tendencies and personality traits are inconclusive, as they show the expected positive signs but do not have a statistically significant impact. This means that while these factors may have a theoretical impact on impulse buying, their practical significance in this specific context remains uncertain. Understanding factors affecting customers’ impulse buying behavior helps the enterprises to design strategies and measures to encourage impulse buying among their customers.